Large‐scale expression profiling and physiological characterization of jasmonic acid‐mediated adaptation of barley to salinity stress - Walia, Harkamal; Wilson, Clyde; Condamine, Pascal; Liu, Xuan; Ismail, Abdelbagi M.; Close, Timothy J. (Wiley, 2007)
Barley (Hordeum vulgare L.) is a salt‐tolerant member of the Triticeae. Recent transcriptome studies on salinity stress response in barley revealed regulation of jasmonic acid (JA) biosynthesis and JA‐responsive genes by salt stress. From that observation and several other physiological reports, it was hypothesized that JA is involved in the adaptation of barley to salt stress. Here we tested that hypothesis by applying JA to barley plants and observing the physiological responses and transcriptome changes. Photosynthetic and sodium ion accumulation responses were compared after (1) salinity stress, (2) JA treatment and (3) JA pre‐treatment followed by salinity stress. The JA‐pre‐treated salt‐stressed plants accumulated strikingly low levels of Na+ in the shoot tissue compared with untreated salt‐stressed plants after several days of exposure to stress. In addition, pre‐treatment with JA partially alleviated photosynthetic inhibition caused by salinity stress. Expression profiling after a short‐term exposure to salinity stress indicated a considerable overlap between genes regulated by salinity stress and JA application. Three JA‐regulated genes, arginine decarboxylase, ribulose 1·5‐bisphosphate carboxylase/oxygenase (Rubisco) activase and apoplastic invertase are possibly involved in salinity tolerance mediated by JA. This work provides a reference data set for further study of the role of JA in salinity tolerance in barley and other plants species.